BRAIN EXTRACTION IN THE LARVARY BIOREGULATOR GAMBUSIA PUNCTATA (POEY, 1854): TECHNICAL ASPECTS OF RESEARCH - Argota, George (2022)
The aim of the study was to describe brain extraction in the larval bioregulator Gambusia punctata (Poey, 1854) as a technical aspect of research. The study was carried out in March 2021 where an area near the mouth of the Almendares River, Havana, Cuba was selected through random probabilistic sampling. The brain extraction in the species G. punctata, was by means of an instrument with two tweezers: holding and dissecting, which allowed manipulation and greater control over the biological sample. The technical aspect of research for the extraction of the brain is as follows: 1st) the individual (male or female) is placed in a ventral position and by means of a smooth stainless steel dissection forceps the containment of the biological sample is carried out, 2nd) with a curved and toothed iris thinker for delicate tissues, the cephalic region is desquamated, and 3rd) visualization and extraction of the brain with a smooth holding forceps until conization is shown in the anatomical region of the brain. In this study, a simple description for brain extraction was shown, which constituted a technical aspect of research that allowed the analysis of enzymatic biomarkers, genetic transcription, histological analysis, DNA molecule, neuropeptides, as well as the bioaccumulation of metals. It is concluded that the technical description of the extraction was simple with which the physiological, morphological and molecular analyses are allowed to verify the survival and, in this case, of the species before their interactions with the environment.